Penerapan Fitur Live Streaming TikTok @Mizzucosmetic untuk Memperkuat Brand Awareness - Made Shanty Aurellia; Bayu Suriaatmaja Suwanda; Alfa Taufan Latif (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study aims to examine how the use of TikTok's live streaming feature on the @mizzucosmetic account can strengthen brand awareness among audiences. This study used a descriptive qualitative method through in-depth interviews and participant observation over four months. There were four informants in this study consisting of two live streamer coordinators, a live host, and a mizzu cosmetics audience who were involved to gain a more comprehensive understanding of the experiences and interaction patterns that occur during live broadcasts. The findings show that interactive features such as live chat, product pins, and flash sales play a role in attracting audience attention, encouraging engagement, and building interest in the products offered. The AIDA theory is used as a framework to examine how live streaming builds attention (Attention), fosters interest and desire (Interest & Desire), and triggers purchasing actions (Action). Overall, this study illustrates that the consistent and informative use of live streaming features can strengthen Mizzu Cosmetics' brand awareness.